Ascorbic Acid Ameriolates Liver Damage by Myeloperoxidase Oxidative Products in a Hamster Model of Amoebic Liver Abscess - Cruz-Baquero, Andrea; Jarillo-Luna, Rosa Adriana; Cárdenas-Jaramillo, Luz María; Drago-Serrano, Maria Elisa; Serrano-Luna, José de Jesús; Pacheco-Yépez, Judith (Frontiers in Cellular and Infection Microbiology, 2022)
Entamoeba histolytica is a protozoan-pathogen-causing amoebic liver abscess (ALA). After amoeba establishment in the liver, it causes abundant infiltrate of neutrophils. Liver tissue damage by neutrophils results in part from anti-amoebic oxidative intermediates, including reactive oxygen species (ROS), reactive nitrogen species (RNS), and hypochlorous acid (HOCl), derived from the myeloperoxidase (MPO) enzyme. Ascorbic acid (ASC) is an antioxidant that acts as a scavenger for ROS and NOS-derived free radicals. No previous information regarding the effect of ASC concerning the participation of MPO in an experimental model of ALA in hamsters has been reported. Thus, the aim of the present work was to analyze the effect of ASC on acute ALA development and to measure the activity and gene expression of the MPO enzyme. Hamsters were treated with ASC (800 mg/kg) and then intrahepatically inoculated with E. histolytica trophozoites. Animals were sacrificed at 3, 6, and 12 h post-inoculation (p.i.), and liver samples were collected. The percentage of lesions, amoeba in situ count, MPO activity, and mpo gene expression were ascertained. Compared to ALA hamsters without ASC treatment as the control group (CT), the ALA group treated with ASC had a significant decrease in liver lesions (all p.i. hours) and viable amoeba count (12 h p.i.) and an increase in MPO activity (12 h p.i.) and mpo gene expression (6 h/12 h p.i.). These data suggest that ASC ameliorated liver damage caused by oxidizing products via modulation of mpo expression and activity.